Effects of different nitrogen concentrations and light intensities on lipid accumulation and growth of Chlamydomonas reinhardtii. Issue 1 (February 2021) - Zhao, Yiran; Li, Zhuoyuan; Tu, Xiaomeng; Xu, Lili
Abstract: This study sets different nitrogen concentration gradients to explore the impact of nitrogen concentration on biomass and lipid accumulation of Chlamydomonas reinhardtii under different light intensities. The results showed that the conditions for the accumulation of lipid in the algae were 30μE-m -2 -s -1 light intensity and 100 mg . mL -1 nitrogen concentration with the lipid content of C. reinhardtii was 39.79% and chlorophyll content was 17.08 mg . mL -1 . This study provides an experimental basis for the regulation of lipid production of C. reinhardtii by using nitrogen-deficient culture and provides a foundation for further utilization of genetic engineering methods to regulate the lipid metabolism of C. reinhardtii.